NILAI EKONOMI PEMANFAATAN LIMBAH KELAPA SAWIT DI KABUPATEN BENGKULU UTARA PROVINSI BENGKULU - Christian Dolli; M Mustopa Romdhon; Reswita Reswita (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2018)
An increase in plantation area will increase the capacity of fresh fruit bunches and increase the quantity of palm oil and palm kernel as processed FFB products. On the other hand, it will also increase the quantity of solid waste, gas waste and liquid waste. At present the various benefits generated are still underestimated so they are not optimized. For this reason, waste from oil palm plantations needs to be assessed economically. Data analysis methods in this study used the technique of productivity change and cost replacement techniques. The results showed that the direct and indirect use value of palm oil waste in North Bengkulu Regency was Rp. 54,024,937,600.12 per month. The results of this assessment can be one of the considerations by the government and related oil palm plantation companies in setting FFB pricing policies.